Forward dynamics simulations provide insight into muscle mechanical work during human locomotion - Neptune, R. R.; McGowan, C. P.; Kautz, S. A. (Exercise and Sport Sciences Reviews, 2009)
Complex musculoskeletal models and computer simulations can provide critical insight into muscle mechanical work output during locomotion. Simulations provide both a consistent mechanical solution that can be interrogated at multiple levels (muscle fiber, musculotendon, net joint moment, and whole-body work) and an ideal framework to identify limitations with different estimates of muscle work and the resulting implications for metabolic cost and efficiency.